Justification revitalizing body of persons "third age" by means of physical education - B.M. Mytskan; N.V. Fedynyak (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : based on sound theoretical analysis and empirical results explain the feasibility of application of physical education for slowing the aging process people "third age". Material : the study included men and women 50 and 60 years, with different rates of aging and indifferent attitude toward physical activity. Results: revealed that the highest number of examinees is aging rapidly accelerated pace. Determined directly proportional relationship between the rate of aging and functionality of the body examined. Established the dominance of biological markers of cardiovascular and respiratory systems in the determination of the aging process of the human body. Conclusions: we recommend the use of exercise for the revitalization of biological aging changes individuals «third age».